2016
DOI: 10.1016/j.joms.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous Heat Production and Preparation Efficiency of Surgical Tungsten Carbide Round Drills: The Effect of Coronectomy on Drill Wear

Abstract: Intraosseous heat produced by surgical tungsten carbide round drills remains under the threshold temperature of bone necrosis for up to 30 coronectomies; however, the use of increased axial pressure (∼ 25 N), especially with the combination of decreased irrigation (∼ 33%), can cause unacceptable temperatures during bone removal. Professionals should select drills and drilling parameters that generate an acceptable amount of heat during surgical tooth removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…For irrigation, room temperature physiologic salt was used, and the amount was set to maximum (~60mL/min) during the entire experiment. A special testing device was able to standardize the following drilling parameters: revolution speed, axial load, and drilling depth, while measuring drilling times automatically [2]. The device was attached to a physiodispenser unit (Implantmed SI-915, W&H, Bürmoos, Austria) and a surgical straight handpiece (SL-11, W&H) ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For irrigation, room temperature physiologic salt was used, and the amount was set to maximum (~60mL/min) during the entire experiment. A special testing device was able to standardize the following drilling parameters: revolution speed, axial load, and drilling depth, while measuring drilling times automatically [2]. The device was attached to a physiodispenser unit (Implantmed SI-915, W&H, Bürmoos, Austria) and a surgical straight handpiece (SL-11, W&H) ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The most optimal bone removal is fast and painless and does not disturb normal healing processes. During drilling, excessive intraosseous heat production can lead to thermal osteonecrosis, which strongly influences the wound healing and regeneration mechanisms, and may lead, e.g., to alveolitis [1, 2]. According to Blum (2002), the incidence of alveolitis can be 25-30% after third molar removals, where drilling is a very frequent procedure [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A), as described in our recent study (20). The apparatus was able to register the exact drilling time and interface with a physio-dispenser unit (Implantmed SI-923; W&H, Bürmos, Austria) and a surgical handpiece (SL-11; W&H).…”
Section: Methodsmentioning
confidence: 99%
“…53,138 Despite the dominant influences of drill bit wear on bone damage, the guidelines regarding this topic in bone drilling have yet to be established. 131 Many studies have reported the effects of drill bit wear on bone damage 11,40,91,108,109,169,178 ; the drill bit wear produces many unwanted complications in bone drilling such as elevating bone temperature above osteonecrosis level, 14,24,40,58,81,108,109,125,156,169,178 plunging into surrounding bone tissues, 9,45 and increasing thrust force and torque. 11,14,106,131,169 Furthermore, drill wear alters bone protein balance 151 and deteriorates-delamination 11 and surface roughness 11,58 -drilling hole quality.…”
Section: Influences Of Drill Bit Conditions On Bone Damage Drill Bit mentioning
confidence: 99%